When Do Firms Generate? Evidence on In-House Electricity Supply in Africa - Steinbuks, J.; Foster, V. (2012)
This paper attempts to identify the underlying causes and costs of own generation of electric power in Africa. Rigorous empirical analysis of 8483 currently operating firms in 25 African countries shows that the prevalence of own generation would remain high (at around 20%) even if power supplies were perfectly reliable, suggesting that other factors such as firms' size, emergency back-up and export regulations play a critical role in the decision to own a generator. The costs of own-generation are about three times as high as the price of purchasing (subsidized) electricity from the public grid. However, because these generators only operate a small fraction of the time, they do not greatly affect the overall average cost of power to industry. The benefits of generator ownership are also substantial. Firms with their own generators report a value of lost load of less than US$50 per hour, compared with more than US$150 per hour for those without. Nevertheless, when costs and benefits are considered side by side, the balance is not found to be significantly positive.